Analisis Arus Kas Kegiatan Operasi dalam Mendeteksi Manipulasi Aktivitas Riil dan Dampaknya Terhadap Kinerja Pasar - Megawati Oktorina; Yanthi Hutagaol (The Indonesian Journal of Accounting Research, 2013)
This study aims to identify firm's tendency to execute real activities manipulation through cash flow from operating activities and its impact to market performance. The sample is drawn from firms in the biggest 50 firms with assets above 1 quintillions rupiahs for period of 2001 - 2006, which are published in Swa100. The research model is based on Roychowdhury's model (2003). Prior to test the hypotheses, this studitthe researcher employed regression model to determine normal and abnormal cash flow from operating activities. The result shows that firms tend to execute real activities manipulation through operating cash flow. Moreover, the impact of real activities manipulation on market performance shows firms which are more likely executing real activities manipulation have higher market performance than their counterparts. By controlling for industrial types of the companies, the result finds that manufacturing firms execute more real activities manipulation than non-manufacturing firms.